Pre-Service Teachers’ Political Conversations on Social Media: Marites–Makabayan Interpretations for Social Studies Education - Mary Joy Supnet; Jerish Anne Espiritu; Kyla Nicolle Oliva; Brix Mirote (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study explored how Filipino pre-service teachers experience and interpret political conversations on social media, distinguish Marites-oriented from Makabayan-oriented discourse, and understand the implications for civic learning, integrated social science education, and their future responsibilities as social studies teachers. Methodology: A qualitative descriptive design was used with eleven second-year pre-service teachers from the College of Teacher Education at President Ramon Magsaysay State University, Castillejos Campus, during the academic year 2025–2026. Individual audio-recorded interviews were conducted through Google Meet or face-to-face according to participant preference and convenience, using an expert-reviewed semi-structured guide. Audio-checked transcripts were manually coded and analyzed thematically using Braun and Clarke’s six-phase procedure, followed by expert theme review and participant member checking; reported English translations were checked by a language expert. Main Findings: Four themes were developed: political talk as everyday digital exposure; participation as selective and emotionally negotiated; distinguishing Marites from Makabayan discourse; and social media as informal civic learning. The themes indicate learning outcomes involving political awareness, reflective participation, source verification, evidence-based judgment, perspective-taking, respectful dialogue, and responsible digital participation. Novelty/Originality of this study: The study advances a culturally grounded Marites–Makabayan framework for examining the credibility, tone, ethics, evidence, and public purpose of online political discourse. As a context-sensitive continuum rather than a fixed binary, the framework contributes to integrated social science education and digital civic pedagogy—teaching that connects interdisciplinary analysis with source evaluation, civic online reasoning, ethical dialogue, and the preparation of future teachers to facilitate controversial public issues responsibly.